Developmental psychopathology from infancy through adolescence - Wenar, Charles 1922-; Kerig, Patricia (McGraw-Hill, 2006)
This accessible, clearly written text approaches child psychopathology as "normal development gone awry" and encourages students to "think developmentally" about psychopathology, from childhood through adolescence. The fifth edition includes cutting-edge research, improved organization, and new coverage of problems that arise in late adolescence/early adulthood.